Genotyping of CYP2D6 Polymorphisms by MALDI-TOF Mass Spectrometry in Sardinian People. (12th May 2013) - Falzoi, Matteo; Pira, Luigi; Lazzari, Paolo; Pani, Luca
Abstract : The CYP2D6 enzyme is involved in the metabolism of many commonly prescribed drugs. The presence of CYP2D6 gene SNPs can alter CYP2D6 enzymatic activity with effects ranging considerably within a population. Objectives . In this study, we have developed a genotyping platform able to determine the alleles related to interindividual variability in the CYP2D6 gene. Design and Methods. We used a long PCR strategy coupled to MALDI-TOF mass spectrometry (Sequenom) to develop a SNPs genotyping method. Furthermore, an amplification allele specific was carried out to infer the correct allelic phase. Results . We tested the multiplex platform in 250 DNA Sardinian samples and found it to be 100% concordant with the sequencing results of our previous work. Conclusions . The MALDI-TOF-based multiplexing system allowed simultaneous and efficient genotyping of a set of CYP2D6 SNPs, evidencing its potential use in diagnostic test development to predict drug responses and clinical outcomes.